Correlation Between Leukocyte Count and Erythrocyte Sedimentation Rate in Pulmonary Tuberculosis Patients at Suai Referral Hospital, Timor Leste - Gunawan, Lucia Sincu; Livrança, Expedito José Oliveira; Ismawatie, Emma (Journal of Indonesian Medical Laboratory and Science, 2025)
Background: Human Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. TB causes serious health problems for about 10 million people each year and is one of the most common causes of death worldwide. The incidence of TB in Indonesia is 354 per 100,000 population, while in Timor-Leste the incidence has stagnated at 498 per 100,000 population. An active TB process may be indicated by an increase in leukocytes and LEDs, whereas an improvement is shown by a decrease in LEDs and normal lecocyte counts. Objectives: This study aimed to determine the correlation between leukocyte count and erythrocyte sedimentation rate (ESR) in pulmonary TB patients at Suai Referral Hospital, Timor-Leste. Materials and Methods: This was an observational analytic study with a cross-sectional approach, conducted from April to June 2023, using medical laboratory records. The study population consisted of pulmonary TB patients who underwent laboratory testing, with a total sampling of 50 patients. Data on leukocyte counts measured using an automated Hematology Analyzer and ESR determined by the Westergren method were tested for normality using the Shapiro-Wilk test, followed by Spearman’s rank correlation test.  Results: The mean leukocyte count was 11.15 ± 5.24 /mm³ and the mean ESR was 63.30 ± 35.71 mm/hour. The correlation test between leukocyte count and ESR showed r = 0.124 (p = 0.392), indicating no significant correlation. Conclusions: There is no significant correlation between leukocyte count and ESR in pulmonary TB patients at Suai Referral Hospital, Timor-Leste.